Glue for reducing phase retardation change of liquid crystal polymer zero-order wave plate as well as preparation method and application of glue

By adjusting the mass ratio of epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate crosslinking agent in the glue, the problem of uneven changes in the phase delay amount of the liquid crystal polymer film layer caused by the existing glue is solved, and a more uniform change in the phase delay amount and higher productivity are achieved.

CN119552581APending Publication Date: 2025-03-04CHANGSHA LUBANG PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411864136.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When the existing glue is bonded to the liquid crystal polymer film layer, the extreme difference of the phase retardation amount is greater than 3 nm, the average value is greater than 15 nm, and the change amount is uneven, which seriously reduces the productivity.

Method used

A glue including epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate crosslinking agent is provided, and by adjusting the mass ratio of these components, especially the proportion of initiators and crosslinking agents, is to speed up the curing rate and reduce the impact on the liquid crystal polymer film layer.

Benefits of technology

The glue is able to achieve high uniformity of the phase delay amount, low change amount and fast curing speed during bonding, which significantly improves the yield of the liquid crystal polymer film layer and reduces the process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193899700000041
    Figure BDA0005193899700000041
  • Figure BDA0005193899700000051
    Figure BDA0005193899700000051
  • Figure BDA0005193899700000052
    Figure BDA0005193899700000052
Patent Text Reader

Abstract

The invention provides glue for reducing phase retardation change of a liquid crystal polymer zero-order wave plate as well as a preparation method and application of the glue, and particularly relates to the technical field of glue. The glue provided by the invention comprises epoxy resin, acrylic acid, a polymerization inhibitor, a photoinitiator and an acrylate cross-linking agent, the mass ratio of the epoxy resin to the acrylic acid to the polymerization inhibitor to the acrylate cross-linking agent is 100: 100: 2: (30-50); the mass ratio of the epoxy resin to the photoinitiator is 100: (4-10). By adjusting the proportion of the initiator and the acrylate cross-linking agent in the glue components in the system, the influence of the glue on a liquid crystal polymer film layer material can be well reduced while the glue curing rate is increased, so that the finally prepared liquid crystal polymer zero-order wave plate has the advantages of high stability and high reliability. And the uniformity and the variation of the retardation amount and the phase retardation amount are both improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glue, and in particular relates to glue for reducing the change of phase delay of a liquid crystal polymer zero-order wave plate, and a preparation method and application thereof. Background Art

[0002] The polymer homogenized diffractive optical element (DOE) is a flat optical element designed based on the principle of diffractive optics, consisting of a liquid crystal polymer and two fused quartz windows. Due to its advantages such as high uniformity, high transmittance, high damage threshold, and sharp edges, it has great use value in multiple application scenarios such as laser medical beauty, laser processing, and surface treatment. However, the design of the three-layer structure requires the use of adhesives for bonding, and the liquid crystal polymer film layer is usually prone to surface thickness modification during this process.

[0003] When using NOA series glue in the actual bonding process, the phase retardation range of the bonded samples is often >3nm, the average value of the phase retardation change is >15nm, the phase retardation change is uneven, and the change is too large. These problems greatly reduce the production yield of the liquid crystal polymer film layer. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a glue for reducing the phase retardation variation of a liquid crystal polymer zero-order wave plate, and a preparation method and application thereof. The glue provided by the present invention has high uniformity of phase retardation and low variation during lamination, and the glue cures quickly.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The present invention provides a glue, which comprises epoxy resin, acrylic acid, a polymerization inhibitor, a photoinitiator and an acrylate cross-linking agent;

[0007] The mass ratio of the epoxy resin, acrylic acid, polymerization inhibitor and acrylate crosslinking agent is 100:100:2:30-50;

[0008] The mass ratio of the epoxy resin to the photoinitiator is 100:4-10.

[0009] Preferably, the mass ratio of the epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate crosslinking agent is 100:100:2:7-10:50.

[0010] Preferably, the epoxy resin includes methyl acrylate epoxy resin ester, ethyl acrylate epoxy resin ester, isobutyl acrylate epoxy resin ester or acrylate epoxy-acrylic acid copolymer.

[0011] Preferably, the methyl acrylate epoxy resin ester includes oxirane-2-acrylate, oxirane-2-yl methyl methacrylate, oxirane-2-yl ethyl acrylate or oxirane-2-yl ethyl methacrylate.

[0012] Preferably, the polymerization inhibitor is a hydroquinone polymerization inhibitor.

[0013] Preferably, the photoinitiator includes at least one of photoinitiator 651, photoinitiator 1173 and photoinitiator TPO.

[0014] Preferably, the acrylate crosslinking agent includes at least one of ethylene glycol diacrylate, butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

[0015] The present invention also provides a method for preparing the glue described in the above technical solution, comprising the following steps:

[0016] The epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate cross-linking agent are mixed to obtain glue.

[0017] The present invention also provides the use of the glue described in the above technical solution as a bonding adhesive in the preparation of a diffractive optical element.

[0018] Preferably, the diffractive optical element comprises a liquid crystal polymer zero-order wave plate.

[0019] The present invention provides a kind of glue, the glue comprises epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate crosslinking agent; the mass ratio of the epoxy resin, acrylic acid, polymerization inhibitor and acrylate crosslinking agent is 100:100:2:30-50; the mass ratio of the epoxy resin and the photoinitiator is 100:4-10. The present invention can well reduce the influence of the glue on the liquid crystal polymer film material while accelerating the curing rate of the glue by adjusting the proportion of the initiator and the acrylate crosslinking agent in the glue component, so that the liquid crystal polymer zero-order wave plate finally obtained, whether it is the uniformity of the delay amount or the change amount of the phase delay amount, is improved and improved, thereby improving the production yield of the liquid crystal polymer film layer and reducing the complexity of the process. It can be seen from the data of the embodiment that the liquid crystal polymer zero-order wave plate prepared by the glue provided by the present invention has a phase delay amount change range of 0.9-1.2nm, and an average value of the phase delay amount change of 5.0-12.9nm. DETAILED DESCRIPTION

[0020] The present invention provides a glue for reducing the phase retardation variation of a liquid crystal polymer zero-order wave plate, the glue comprising epoxy resin, acrylic acid, a polymerization inhibitor, a photoinitiator and an acrylate crosslinking agent;

[0021] The mass ratio of the epoxy resin, acrylic acid, polymerization inhibitor and acrylate crosslinking agent is 100:100:2:30-50;

[0022] The mass ratio of the epoxy resin to the photoinitiator is 100:4-10.

[0023] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.

[0024] In the present invention, the epoxy resin preferably includes methyl acrylate epoxy resin ester, ethyl acrylate epoxy resin ester, isobutyl acrylate epoxy resin ester or acrylate epoxy-acrylic acid copolymer. In the present invention, the methyl acrylate epoxy resin ester preferably includes oxirane-2-acrylate, oxirane-2-yl methyl methacrylate, oxirane-2-yl ethyl acrylate or oxirane-2-yl ethyl methacrylate

[0025] In the present invention, the polymerization inhibitor is preferably a hydroquinone polymerization inhibitor, and the hydroquinone polymerization inhibitor preferably includes at least one of hydroquinone, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butylhydroquinone and 2-tert-butylhydroquinone.

[0026] In the present invention, the photoinitiator preferably includes at least one of photoinitiator 651, photoinitiator 1173 and photoinitiator TPO.

[0027] In the present invention, the acrylate crosslinking agent preferably includes at least one of ethylene glycol diacrylate, butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

[0028] In the present invention, the mass ratio of the epoxy resin, acrylic acid, inhibitor and acrylate crosslinking agent is 100:100:2:30-50. In a specific embodiment, the mass ratio of the epoxy resin, acrylic acid, inhibitor and acrylate crosslinking agent can be 100:100:2:30, 100:100:2:35, 100:100:2:40, 100:100:2:45 or 100:100:2:50.

[0029] In the present invention, the mass ratio of the epoxy resin to the photoinitiator is 100:4-10. In a specific embodiment, the mass ratio of the epoxy resin to the photoinitiator can be 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10. By adjusting the proportion of each component of the glue in the system, the curing rate of the glue can be accelerated while the influence of the glue on the liquid crystal polymer film material can be well reduced.

[0030] The present invention also provides a method for preparing the glue described in the above technical solution, comprising the following steps:

[0031] The epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate cross-linking agent are mixed to obtain glue.

[0032] In the present invention, the mixing is preferably carried out under stirring conditions, and the stirring speed is preferably 1400-1600 rpm. In a specific embodiment, the stirring speed may be 1400 rpm, 1500 rpm or 1600 rpm; the stirring time is preferably 4-6 min. In a specific embodiment, the stirring time may be 4 min, 5 min or 6 min.

[0033] In the present invention, the mixing preferably further comprises standing for degassing.

[0034] The present invention also provides the use of the glue prepared by the preparation method described in the above technical solution as a bonding adhesive in the preparation of a diffractive optical element.

[0035] In the present invention, the diffractive optical element preferably includes a liquid crystal polymer zero-order wave plate.

[0036] The present invention has no special requirements on the application method, and the commonly used technical means in the field can be adopted.

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in conjunction with specific embodiments below. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any modification, equivalent replacement, improvement, etc. made to the implementation methods of the present invention based on the technical essence and general principles of the present invention without creative work should be within the scope of protection of the present invention.

[0038] Example 1

[0039] Ethylene oxide-2-acrylate, acrylic acid, hydroquinone, photoinitiator 651, and 1,5-pentanediol diacrylate were prepared in a mass ratio of 100:100:2:4:50, stirred with an electric stirrer at 1500 rpm for 5 minutes, and degassed at rest to obtain glue.

[0040] Soak a 25.4*3mm fused quartz substrate in acetone, put it into an ultrasonic cleaner for 5 minutes, take it out and put it into anhydrous ethanol for 5 minutes, take it out and put it into ultrapure water for 5 minutes, then put it into an oven at 60℃ for drying, and then irradiate it with ultraviolet light with a power of 10mW and a wavelength of 254nm for 5 minutes.

[0041] The treated fused quartz substrate was placed on a spin coating machine, and a negative pressure vacuum adsorption was used to absorb a 20 wt% photoinduced alignment agent SD1-DMF solution with a syringe, and 0.1 mL was dropped on the substrate. After spin coating at 3000 rpm for 30 seconds, it was placed on a 100°C hot plate for 3 minutes and stored in a nitrogen cabinet at room temperature.

[0042] The substrate coated with the photoinducer was placed under a power density of 4 mW / cm 2 Expose to a polarized blue LED light source for 3 min and store in a nitrogen cabinet at room temperature.

[0043] Liquid crystal monomer M1, photoinitiator 651 and chlorobenzene were mixed at a mass ratio of 15:1, and ultrasonically stirred to obtain a 35wt% liquid crystal solution, which was stored in a constant temperature box at 50°C. The exposed substrate was placed on a spin coating machine, and 0.1mL was dripped onto the exposed substrate using a negative pressure vacuum adsorption machine. After spin coating at 3000rpm for 30s, the exposed substrate was heated to 5mW / cm 2 The mixture was cured under ultraviolet light for 3 minutes to obtain a liquid crystal polymer.

[0044] The uniformly aligned liquid crystal polymer after solidification was placed on the phase delay test platform for testing and relevant test data was collected. After dripping 0.5 mL of glue at the center of the liquid crystal polymer, a clean fused quartz substrate was placed on top and pressure was applied to remove the bubbles in the interlayer. 2 Curing under ultraviolet light for 1 minute to obtain a liquid crystal polymer zero-order wave plate.

[0045] The liquid crystal polymer zero-order wave plate was placed on a phase retardation test platform, and different positions were tested to collect relevant test data. The liquid crystal polymer zero-order wave plate was then aged at 50°C for 24 hours, and the phase retardation was tested at the same point to collect relevant test data. Table 1 was plotted.

[0046] Table 1 Phase retardation variation of liquid crystal polymer zero-order wave plate prepared by using the glue obtained in Example 1

[0047]

[0048]

[0049] From the data in Table 1, it can be calculated that the average value of the delay change is 12.826nm (indicating a low change in the phase delay), and the extreme value of the delay change is 1.124nm (a small extreme value indicates a high uniformity of the phase delay). The calculation of the average value of the delay change is shown in Formula 1:

[0050] The average value of the change in delay amount = [(the maximum value of the average value before bonding - the maximum value of the average value after aging at 50°C for 24 hours) + (the minimum value of the average value before bonding - the minimum value of the average value after aging at 50°C for 24 hours)] / 2 Formula 1;

[0051] The calculation of the delay variation range is shown in Formula 2:

[0052] The extreme value of the delay variation = (the maximum value of the average value before bonding - the maximum value of the average value after aging at 50°C for 24 hours) - (the minimum value of the average value before bonding - the minimum value of the average value after aging at 50°C for 24 hours) Formula 2.

[0053] By comparing and calculating the measured values ​​before lamination and the measured values ​​after aging, it can be known that the glue prepared by the present invention has little effect on the liquid crystal polymer film layer, and the liquid crystal polymer film layer is not easy to change.

[0054] By comparing the data after bonding and the data after aging, it can be seen that the smaller the difference between the two, the better the glue stability.

[0055] Example 2

[0056] Ethylene oxide-2-acrylate, acrylic acid, hydroquinone, photoinitiator 651, and 1,5-pentanediol diacrylate were prepared in a mass ratio of 100:100:2:7:50, and other conditions were the same as in Example 1.

[0057] The liquid crystal polymer zero-order wave plate was placed on a phase retardation test platform, and different positions were tested to collect relevant test data. The liquid crystal polymer zero-order wave plate was then aged at 50°C for 24 hours, and the phase retardation was tested at the same point to collect relevant test data. Table 2 was plotted.

[0058] Table 2 Phase retardation variation of liquid crystal polymer zero-order wave plate prepared by using the glue obtained in Example 2

[0059]

[0060]

[0061] From the data in Table 2, it can be calculated that the average value of the delay change is 8.037nm, and the extreme value of the delay change is 0.945nm.

[0062] Example 3

[0063] Methyl 2-oxirane acrylate, acrylic acid, hydroquinone, photoinitiator 651, and 1,5-pentanediol diacrylate were prepared in a mass ratio of 100:100:2:10:50, and other conditions were the same as those in Example 1.

[0064] The liquid crystal polymer zero-order wave plate was placed on a phase retardation test platform, and different positions were tested to collect relevant test data. The liquid crystal polymer zero-order wave plate was then aged at 50°C for 24 hours, and the phase retardation was tested at the same point to collect relevant test data. Table 3 was plotted.

[0065] Table 3 Phase retardation variation of liquid crystal polymer zero-order wave plate prepared by the glue obtained in Example 3

[0066] Before Lamination Point 1 / nm Point 2 / nm Point 3 / nm Average value / nm Sample 1 2.109 1.002 1.862 1.657667 Sample 2 2.109 4.578 4.578 3.755 After bonding Sample 1 -1759 0.298 -1.183 -0.88133 Sample 2 -1.348 1.862 2.109 0.874333 Aging at 50℃ for 12h Sample 1 -2.582 -3.158 -2.747 -2.829 Sample 2 -2.829 0.792 -0.525 -0.854 50℃ aging 24h Sample 1 -3.104 -4.173 -2.509 -3.262 Sample 2 -3.022 -0.062 -3.187 -2.09033

[0067] From the data in Table 3, it can be calculated that the average value of the delay change is 5.383nm, and the extreme value of the delay change is 0.926nm.

[0068] Comparative Example 1

[0069] The liquid crystal polymer zero-order wave plate was prepared using NOA-61 glue, and other conditions were the same as those in Example 1.

[0070] The liquid crystal polymer zero-order wave plate was placed on a phase delay test platform, and different positions were tested to collect relevant test data. The liquid crystal polymer zero-order wave plate was then aged at 50°C for 12 hours, and the phase delay was tested at the same point to collect relevant test data. Table 4 was plotted.

[0071] Table 4 Phase retardation variation of liquid crystal polymer zero-order wave plate prepared by using the glue obtained in Comparative Example 1

[0072] Before Lamination Point 1 / nm Point 2 / nm Point 3 / nm Average value / nm Sample 1 5.092 5.751 6.163 5.6686667 Sample 2 5.092 3.938 4.681 4.570333 Sample 3 8.719 5.998 9.461 8.059333 Sample 4 7.565 6.741 5.669 6.658333 Sample 5 3.361 4.102 5.009 4.157333 Aging at 50℃ for 12h Sample 1 -2.081 -1.173 -1.503 -1.58567 Sample 2 -2.741 -2.327 -1.915 -2.32767 Sample 3 -6.284 -9.994 -8.757 -8.345 Sample 4 -2.741 -2.575 -2.081 -2.46567 Sample 5 -9.087 -7.026 -10.406 -8.82967 50℃ aging 24h Sample 1 -14.088 -18.471 -18.306 -16.955 Sample 2 -18.389 -16.901 -16.983 -17.4243 Sample 3 -21.366 -23.434 -23.103 -22.6343 Sample 4 -18.721 -17.644 -16.817 -17.7273 Sample 5 -21.954 -20.374 -22.524 -21.6143

[0073] From the data in Table 4, it can be calculated that the average value of the delay change is 25.094nm, and the extreme value of the delay change is 8.699nm.

[0074] Comparative Example 2

[0075] The liquid crystal polymer zero-order wave plate was prepared using NOA-63 glue, and other conditions were the same as those in Example 1.

[0076] The liquid crystal polymer zero-order wave plate was placed on a phase delay test platform, and different positions were tested to collect relevant test data. The liquid crystal polymer zero-order wave plate was then aged at 50°C for 12 hours, and the phase delay was tested at the same point to collect relevant test data. Table 5 was plotted.

[0077] Table 5 Phase retardation changes of liquid crystal polymer zero-order wave plates prepared using the glue obtained in Comparative Example 2

[0078]

[0079]

[0080] From the data in Table 5, it can be calculated that the average value of the delay change is 24.892nm, and the extreme value of the delay change is 10.31nm.

[0081] Comparative Example 3

[0082] The liquid crystal polymer zero-order wave plate was prepared using NOA-68 glue, and other conditions were the same as those in Example 1.

[0083] The liquid crystal polymer zero-order wave plate was placed on a phase delay test platform, and different positions were tested to collect relevant test data. The liquid crystal polymer zero-order wave plate was then aged at 50°C for 12 hours, and the phase delay was tested at the same point to collect relevant test data. Table 6 was plotted.

[0084] Table 6 Phase retardation variation of liquid crystal polymer zero-order wave plate prepared by the glue obtained in Comparative Example 3

[0085]

[0086]

[0087] From the data in Table 6, it can be calculated that the average value of the delay change is 15.915nm, and the extreme value of the delay change is 3.885nm.

[0088] From the above results, when NOA-61, NOA-63 and NOA-68 glues are used for the bonding process, the range values ​​of the phase delay of the samples after bonding are 8.699nm, 10.31nm and 3.885nm, respectively, which greatly reduces the production yield, while the range value of the phase delay of the samples after bonding with the glue prepared by the present invention is 0.926~1.124nm, indicating that the phase delay has high uniformity and the production yield has been greatly improved. In addition, the average values ​​of the phase delay changes of the liquid crystal polymer zero-order wave plates prepared in Comparative Examples 1 to 3 are 25.094nm, 24.892nm and 15.915nm, respectively. The preparation of standard liquid crystal polymer polarization grating samples needs to be controlled within the range of ±5nm near the λ / 2 phase delay at a specific wavelength. Therefore, when using the NOA series glue to design and produce, the phase delay needs to be set to +20nm to meet the sample preparation requirements, resulting in great inconvenience and a reduction in production yield. The optimal average value of the phase retardation change of the liquid crystal polymer zero-order wave plate prepared by the glue obtained in the present invention is 5.383nm, which is closer to the λ / 2 phase retardation at a specific wavelength, greatly reducing the complexity of the production process.

[0089] The glue prepared by the present invention accelerates the curing rate of the glue by effectively adjusting the proportion of the initiator in the glue component system, and can well reduce the influence of the glue on the liquid crystal polymer film layer material. The prepared liquid crystal polymer zero-order wave plate has improved and enhanced uniformity and variation of delay amount and phase delay amount.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A glue, characterized in that: The glue comprises epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate cross-linking agent; The mass ratio of the epoxy resin, acrylic acid, polymerization inhibitor and acrylate crosslinking agent is 100:100:2:30-50; The mass ratio of the epoxy resin to the photoinitiator is 100:4-10.

2. The glue according to claim 1, characterized in that The mass ratio of the epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate crosslinking agent is 100:100:2:7-10:

50.

3. The glue according to claim 1, characterized in that The epoxy resin includes methyl acrylate epoxy resin ester, ethyl acrylate epoxy resin ester, isobutyl acrylate epoxy resin ester or acrylate epoxy-acrylic acid copolymer.

4. The glue according to claim 3, characterized in that: The methyl acrylate epoxy resin ester includes oxirane-2-acrylate, oxirane-2-yl methyl methacrylate, oxirane-2-yl ethyl acrylate or oxirane-2-yl ethyl methacrylate.

5. The glue according to claim 1, characterized in that: The polymerization inhibitor is a hydroquinone polymerization inhibitor.

6. The glue according to claim 1, characterized in that The photoinitiator includes at least one of photoinitiator 651, photoinitiator 1173 and photoinitiator TPO.

7. The glue according to claim 1, characterized in that The acrylate crosslinking agent includes at least one of ethylene glycol diacrylate, butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

8. The method for preparing the glue according to any one of claims 1 to 7, characterized in that: The following steps are involved: The epoxy resin, acrylic acid, polymerization inhibitor, photoinitiator and acrylate cross-linking agent are mixed to obtain glue.

9. Use of the glue described in any one of claims 1 to 7 or the glue prepared by the preparation method described in claim 8 as a bonding adhesive in the preparation of a diffractive optical element.

10. The use according to claim 9, characterized in that: The diffractive optical element includes a liquid crystal polymer zero-order wave plate.

Citation Information

Cited By

  • Glue and application thereof, and preparation method of optical element

    CN120623915A

  • UV photocuring glue, preparation method and application thereof, and preparation method of liquid crystal micro-nano optical element

    CN121471858A